The prevalence of darunavir-associated mutations in HIV-1-infected children in the UK. - Donegan, K; Walker, A; Dunn, D; Judd, A; Pillay, D; Menson, E; Lyall, H; Tudor-Williams, G; Gibb, D (2012)
BACKGROUND: We examined the prevalence of ritonavir-boosted darunavir (DRV) resistance-associated mutations (RAMs) in HIV-infected children in the UK to determine the drug's potential clinical utility as a first-line or second-line protease inhibitor (PI). METHODS: The prevalence of DRV RAMs, identified from IAS 2010 and Stanford, and the Stanford susceptibility score, were estimated in PI-naive and PI-experienced children in the Collaborative HIV Paediatric Study and the UK HIV Drug Resistance Database 1998-2008. Associations between type/duration of PI exposure and area under the viraemia curve on PI with the number of RAMs were investigated using multivariate Poisson regression. RESULTS: A total of 17/417 (4%) children with a resistance test when PI-naive had one IAS DRV RAM, and 1 had a Stanford mutation; none had multiple DRV RAMs. A total of 177 PI-experienced children had a test after a median 2.7 years (IQR 1.1-5.2) on PIs; 19 (11%) had one IAS DRV RAM, 7 (4%) had two RAMs, 1 (0.6%) had three RAMs and 1 (0.6%) had four RAMs. DRV RAMs were independently associated with increased years on a PI, a larger area under the viraemia curve since starting PIs, and any exposure to PIs other than lopinavir (all P≤0.05). Only 6 (3%) PI-experienced children had intermediate-level DRV/ritonavir resistance; none had high-level resistance. CONCLUSIONS: DRV resistance was negligible in PI-naive children and those with lopinavir PI exposure alone. However resistance increased with increasing time, and with higher levels of viraemia, on PIs. Once-daily DRV/ritonavir would be valuable as a second PI or an alternative first PI, particularly if coformulated with a booster in an appropriate formulation for children.